Hydroxamic acids: new players in the multifactorial mechanisms of maize resistance to Striga hermonthica - Marcotrigiano, R.A.; Carluccio, A.V.; Unachukwu, N.; Adeoti, S.R.; Abdulsalam, T.; Gedil, M.; Menkir, A.; Gisel, A.; Stavolone, L. (Elsevier, 2023)
Striga hermonthica is the most widespread and destructive plant parasite infesting maize and other major crops in sub-Saharan Africa where it causes severe yield losses and threatens food security. Several tolerant maize lines supporting reduced S. hermonthica emergence have been deployed. However, the molecular bases of such resistance are yet poorly understood. Based on a time course comparative gene expression analysis between susceptible and resistant maize lines we have confirmed resistance mechanisms known to be activated upon plant parasite infestation and identified potential novel players worth further investigation e.g. iron homeostasis and mitochondrial respiration-related genes. Most intriguingly, we show a previously unknown strategy of maize post-attachment resistance based on DIMBOA accumulation in S. hermonthica-infested maize roots. S. hermonthica infestation triggers positive regulation of gene expression in the hydroxamic acid (HA) pathway culminating with an accumulation of benzoxazinoids (BX), known for their antifeedant, insecticidal, antimicrobial, and allelopathic activities. We demonstrate that HA root content is positively correlated with S. hermonthica resistance in the resistant parent and its progenies and in unrelated maize lines. Downregulation of HA genes causes increased susceptibility to S. hermonthica infestation in loss-of-function maize mutants. While the mechanism of BX action in parasitic plant resistance is yet to be uncovered, the potential of this discovery for developing effective control and breeding strategies is enormous.